Concentrations of matrix metalloproteinases and their tissue inhibitors in the cerebrospinal fluid of patients with Alzheimer's disease - Mroczko, Barbara; Groblewska, Magdalena; Zboch, Marzena; Kulczynska, Agnieszka; Koper, Olga M.; Szmitkowski, Maciej; Kornhuber, Johannes; Lewczuk, Piotr (Journal of Alzheimer's Disease, 2014)
A growing body of evidence shows the involvement of matrix metalloproteinases (MMPs) and their tissue inhibitors (TIMPs) in neurodegeneration processes, but reports of their concentrations in the cerebrospinal fluid (CSF) are inconsistent.Therefore, the aim of our study was to evaluate the CSF concentrations of MMP-2, MMP-3, MMP-9, and their inhibitors (TIMP-1 and TIMP-2) in carefully selected groups of patients with Alzheimer's disease (AD), mild cognitive impairment (MCI), and non-demented controls, whose clinical and neuropsychological diagnoses were confirmed by the corresponding CSF biomarkers of neurochemical dementia diagnostics: decreased concentrations of A?1-42 and/or A?42/40 ratio, and increased concentrations of Tau and pTau181 proteins.The study included 33 AD patients, 15 subjects with MCI, and 18 elderly individuals without cognitive deficits. The CSF concentrations of MMPs and TIMPs were determined with ELISAs.CSF concentrations of MMP-9 were significantly lower, and the concentrations of MMP-3 significantly higher in AD patients compared to the controls. Neither MMP-2 nor TIMPs showed significant changes among the groups investigated.Altered concentrations of two out of three MMPs investigated in this study suggest that this family of biomolecules may play a role in the AD pathophysiology. Further studies are needed to establish their potential diagnostic utility.
EVALuna2:23631